Experimental study on proppant placement in rough fractures with shear slippage in shale reservoirs - ZHANG Tao, CHEN Hongli, WANG Kun, GOU Haoran, ZHANG Yifan, TANG Tang, ZHOU Hangyu, ZUO Hengbo (Youqicang pingjia yu kaifa)
Under the influence of fracture shear slippage and wall roughness, the fluid flow channels within the fractures are uneven, making the transport and placement patterns of proppant carried by fracturing fluids more complex. Using core samples from the Longmaxi Formation, rock fracture surfaces were obtained through splitting, and rough fracture plates were created using techniques such as stretching, stacking, and carving to construct an experimental setup for proppant transport in single-sided rough fractures. Semi-quantitative tests of sand dam morphology and quantitative tests of solid-liquid two-phase flow were conducted. Experiments on proppant transport were carried out under conditions of varying roughness, discharge, viscosity, and particle size within the uneven flow channels of rough fractures. Additionally, particle image velocimetry (PIV) / particle tracking velocimetry (PTV) tests were performed in the fracture near-wellbore area under different roughness conditions. Results showed that the flow channels in rough fractures were uneven, and the proppant placement morphology exhibited an irregular concave-like structure, influenced by dominant channels. When fluids and proppants flowed near large protrusions, their original movement direction was altered towards dominant channels. The movement direction of the proppants was also affected by the accumulated sand dam morphology. Discharge was the key factor in reducing the influence of dominant channels, where decreasing discharge could effectively plug these channels. Under varying viscosity and particle size conditions, the influence of dominant channels persisted, with viscosity and particle size mainly affecting the transport distance and accumulation pattern of the proppants. Increased viscosity or reduced particle size led to greater proppant transport distances and layered sand dam accumulation.